Genetic and clinical characteristics including occurrence of testicular adrenal rest tumors in Slovak and Slovenian patients with congenital adrenal hyperplasia due to 21-hydroxylase deficiency - Saho, Robert; Dolzan, Vita; Zerjav Tansek, Mojca; Pastorakova, Andrea; Petrovic, Robert; Knapkova, Maria; Trebusak Podkrajsek, Katarina; Suput Omladic, Jasna; Bertok, Sara; Avbelj Stefanija, Magdalena; Kotnik, Primoz; Battelino, Tadej; et al. (Frontiers in Endocrinology, 2023)
OBJECTIVE: To analyze the mutational spectrum, clinical characteristics, genotype–phenotype correlations, testicular adrenal rests tumor prevalence, and the role of neonatal screening in congenital adrenal hyperplasia (CAH) patients from Slovakia and Slovenia. DESIGN AND METHODS: Data were obtained from 104 patients with CAH registered in Slovak and Slovenian databases. Low-resolution genotyping was performed to detect the most common point mutations. To detect deletions, conversions, point mutations, or other sequence changes in the CYP21A2 gene, high-resolution genotyping was performed. Genotypes were classified according to residual 21-hydroxylase activity (null, A, B, C). RESULTS: 64% of the individuals had the salt-wasting form (SW-CAH), 15% the simple virilizing form (SV-CAH), and 21% the non-classic (NC-CAH). CYP21A2 gene deletion/conversion and c.293-13A/C>G pathogenic variant accounted together for 55.5% of the affected alleles. In SV-CAH p.Ile172Asn was the most common pathogenic variant (28.13%), while in NC-CAH p.Val282Leu (33.33%), CYP21A2 gene deletion/conversion (21.43%), c.293-13A/C>G (14.29 %), Pro30Leu (11.90%). The frequency of alleles with multiple pathogenic variants was higher in Slovenian patients (15.83% of all alleles). Severe genotypes (0 and A) correlated well with the expected phenotype (SW in 94.74% and 97.3%), while less severe genotypes (B and C) correlated weaklier (SV in 50% and NC in 70.8%). The median age of SW-CAH patients at the time of diagnosis was 6 days in Slovakia vs. 28.5 days in Slovenia (p=0.01). Most of the Slovak patients in the cohort were detected by NBS. (24 out of 29). TARTs were identified in 7 out of 24 male patients, of whom all (100 %) had SW-CAH and all had poor hormonal control. The median age at the diagnosis of TARTs was 13 years. CONCLUSION: The study confirmed the importance of neonatal screening, especially in the speed of diagnosis of severe forms of CAH. The prediction of the 21-OH deficiency phenotype was reasonably good in the case of severe pathogenic variants, but less reliable in the case of milder pathogenic variants, which is consistent compared to data from other populations. Screening for TARTs should be realized in all male patients with CAH as remission is possible when identified early.